2017
DOI: 10.1016/j.ibiod.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of phenanthrene and benzene using microbial fuel cells operated continuously for possible in situ and ex situ applications

Abstract: Bioelectrochemical systems could have potential for bioremediation of contaminants either in situ or ex situ. The treatment of a mixture of phenanthrene and benzene using two different tubular microbial fuel cells (MFCs) designed for either in situ and ex situ applications in aqueous systems was investigated over long operational periods (up to 155 days). For in situ deployments, simultaneous removal of the petroleum hydrocarbons (>90% in term of degradation efficiency) and bromate, used as catholyte, (up to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…The maximum power densities obtained in this study were comparable to the reported values in the literature for treatment of phenanthrene and benzene, as well as benzene‐ and ammonium‐contaminated groundwater in MFCs, that is, ~25–300 mW/m 3 (Adelaja et al, ; Wei et al, ). Groundwater is often contaminated by a variety of organic and inorganic contaminants, for example, 1,4‐dioxane is often found co‐contaminated with chlorinated hydrocarbons (e.g., TCE and TCA; Stefan & Bolton, ; Zhang, Gedalanga, & Mahendra, ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The maximum power densities obtained in this study were comparable to the reported values in the literature for treatment of phenanthrene and benzene, as well as benzene‐ and ammonium‐contaminated groundwater in MFCs, that is, ~25–300 mW/m 3 (Adelaja et al, ; Wei et al, ). Groundwater is often contaminated by a variety of organic and inorganic contaminants, for example, 1,4‐dioxane is often found co‐contaminated with chlorinated hydrocarbons (e.g., TCE and TCA; Stefan & Bolton, ; Zhang, Gedalanga, & Mahendra, ).…”
Section: Resultssupporting
confidence: 87%
“…Microbial fuel cell (MFC) is a special type of bioelectrochemical system with no supply of external voltage, but instead, generation of renewable energy from the water treatment process. Previously, different types of toxic and recalcitrant organic pollutants, such as benzene, phenol, naphthalene, phenanthrene, and furfural, have been effectively treated through oxidative processes in anode chambers of MFCs, and maximum power densities of 7–220 mW/m 2 have been achieved (Adelaja, Keshavarz, & Kyazze, ; Wang, Luo, Fallgren, Jin, & Ren, ; Zhou et al, ). Besides, MFCs have been utilized to treat groundwater polluted by both organic contaminants, such as benzene and phenolic compounds in anode chambers, as well as inorganic contaminants, such as nitrate, perchlorate, and Cr(VI) in cathode chambers (Butler, Clauwaert, Green, Verstraete, & Nerenberg, ; Hedbavna, Rolfe, Huang, & Thornton, ; Liu, Lai, Ye, & Lin, ; Pous, Puig, Coma, Balaguer, & Colprim, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kirmizakis et al 2019 In situ treatment of phenantrene and benzene contaminated groundwater with a MFC was reported by Adelaja et al (2017), where a tubular MFC was designed with carbon felt anode exposed to the contaminated groundwater and used for long term operation (about 155 days) ( Figure 2F). The system was able to remove up to 90% petroleum hydrocarbons at the anode and up to 79% bromate (BrO3 -) at the cathode (added as catholyte).…”
Section: In Situ Bioelectroremediation: the Quest For The Ideal Setupmentioning
confidence: 99%
“…MFCs could be employed in the treatment of these recalcitrant pollutants with concomitant bioelectricity generation (Morris and Jin, 2012). The treatment of a mixture of phenanthrene and benzene using two different tubular microbial fuel cells (MFCs) were designed for either in situ and ex situ applications in aqueous systems over long periods (up to 155 days) (Adelaja et al, 2017). Simultaneous removal of the petroleum hydrocarbons (>90 % in term of degradation efficiency) and bromate, used as catholyte (up to 79 %) with concomitant biogenic electricity generation (peak power density up to 6.75 mW m -2 ) were obtained at a hydraulic retention time (HRT) of 10 days for in situ studies.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%